The relationship between neurocysticercosis and epilepsy: an endless debate - Arturo Carpio; Matthew L. Romo (Arquivos de Neuro-Psiquiatria)
Neurocysticercosis (NC), or cerebral infection with Taenia solium, is an important public health problem worldwide. Among the neurological sequelae of NC, seizures have been described as the most common symptom. Acute symptomatic seizures often result from degeneration of a viable cyst; however, not all of these patients with acute or provoked seizures will develop epilepsy (i.e., recurrent unprovoked seizures). Because of the high prevalence of epilepsy and NC, a causal, as well as incidental relationship between the two may exist. The epileptogenicity of calcified cysts as well as the potential association between NC and hippocampal sclerosis necessitates future research. Antihelminthic treatment of NC results in disappearance of viable cysts in about one-third of patients with parenchymal disease, but a reduction in seizure recurrence has not been demonstrated in randomized controlled trials. Prevention is critical to reduce the burden of seizure and epilepsy related to NC.